Efeitos agudos de diferentes protocolos de treinamento resistido na modulação autonômica cardíaca de mulheres hipertensas - Vale, Arthur Ferreira do (2018)
Introduction: Arterial hypertension (AH) is the main risk factors for cardiovascular diseases. The practice of high intensity resistance training (RT) may be an alternative for the control of AH. However, it is necessary to define which RT protocol is most appropriate for patients with hypertension: to use protocols with higher loads and fewer repetitions or with lower loads and greater number of repetitions. Individuals with AH have an imbalance in the autonomic nervous system (ANS) and it is possible that TR may accentuate such changes. Among the techniques used to evaluate the ANS, heart rate variability (HRV) appears as a simple and non-invasive measure of cardiovascular risk assessment. Aims: To analyze and compare the effects of different high intensity resistance training protocols on hemodynamic parameters and cardiac autonomic modulation of hypertensive women. Methods: Crossover randomized clinical trial of 15 middleaged women (45-69 years) and controlled hypertensives who underwent two different resistance training protocols (6 maximal repetitions and 15 maximal repetitions). HRV was collected through intervals between consecutive heart beats (R-R interval) in the supine position before each protocol, immediately after, 1 hour after and 24 hours after each protocol. The repeated-measures ANOVA was used to evaluate changes in heart rate variability in the different times and protocols used, the value of p≤0.05 was considered significant. Results: The indices that compose HRV (low frequency, high frequency and ratio) were not significant between the control session and the session of 6 maximal repetitions (p≥0.05), however, the low frequency values were higher and lower frequency for the session of 15 maximal repetitions when compared to the control session (p≤0.05). Conclusion: In the comparison between the two protocols the one with the highest volume promoted greater cardiovascular stress while the one with the lowest volume did not show significant differences when compared to the control session.